Pemberdayaan Wakaf Tunai Produktif Al-Washliyah Cirebon Sebagai Upaya Terwujudnya Kesejahteraan Jama’ah - Zaenal Masduqi; Alvien Septian Haerisma (Dimasejati: Jurnal Pengabdian Kepada Masyarakat, 2023)
EMPOWERMENT OF PRODUCTIVE AL-WASHLIYAH CIREBON CASH WAQF AS AN EFFORT TO REALIZE JAMA'AH WELFARE. Sociologically, the people's understanding of waqf assets is still limited to land, buildings and other immovable objects. Its use is limited to the establishment of mosques, madrasas, Islamic boarding schools and public cemeteries. This understanding continues to grow to this day, although this does not violate its useful function. Philanthropically, cash waqf is directed to economic development and empowerment in order to increase the economic welfare of the people. These problems arise due to the lack of transformative preaching about the importance of cash waqf and the various examples of the benefits of waqf carried out by Islamic organizations in general. The role of productive cash waqf needs to be understood and practiced as a form of empowering the potential possessed by Al-Washliyah Cirebon such as renting waqf kiosks and waqf pools so that the proceeds are used for other purposes. This practice is expected to generate widespread prosperity and can be enjoyed by the congregation of Al-Washliyah Cirebon. The empowerment methodology is carried out through a targeted approach by reviving waqf land which has so far been ineffective. Through empowering waqf, waqf assets become profitable assets, of course by involving the community both individually and in groups to carry out cash waqf movements.